2015
DOI: 10.1111/bjh.13492
|View full text |Cite
|
Sign up to set email alerts
|

Stromal CYR61 Confers Resistance to Mitoxantrone via Spleen Tyrosine Kinase Activation in Human Acute Myeloid Leukaemia

Abstract: Summary Approximately 50% of children with acute myeloid leukaemia (AML) relapse, despite aggressive chemotherapy. The bone marrow stromal environment protects leukaemia cells from chemotherapy (i.e., stroma-induced chemoresistance), eventually leading to recurrence. Our goal is to delineate the mechanisms underlying stroma-mediated chemoresistance in AML. We used two human bone marrow stromal cell lines, HS-5 and HS-27A, which are equally effective in protecting AML cells from chemotherapy-induced apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 46 publications
(73 reference statements)
5
58
0
Order By: Relevance
“…Our results showed that Cyr61 in CML BM decreased the apoptosis of CML cells induced by IM. The findings reported here are consistent with previous reports, in which Cyr61 blocks antitumor drug‐induced apoptosis of cancer cells, resulting in chemotherapy resistance in breast cancer, cervical cancer, and AML . An important observation was that inhibition of Cyr61 restored the chemosensitivity of CML cells to IM in a mouse model of CML.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that Cyr61 in CML BM decreased the apoptosis of CML cells induced by IM. The findings reported here are consistent with previous reports, in which Cyr61 blocks antitumor drug‐induced apoptosis of cancer cells, resulting in chemotherapy resistance in breast cancer, cervical cancer, and AML . An important observation was that inhibition of Cyr61 restored the chemosensitivity of CML cells to IM in a mouse model of CML.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that Cyr61 decreases the apoptosis induced by anticancer drugs in breast cancer cells, ovarian carcinoma cells, renal cell carcinoma, and AML, suggesting that Cyr61 is linked to chemotherapy resistance in tumors. However, whether Cyr61 is involved in chemoresistance in CML has not been reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 Since mitoxantrone is used in current upfront pediatric AML treatment protocols in North America, this finding is potentially clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our prior finding that environment-induced mitoxantrone resistance is driven primarily by soluble factors as opposed to stromal contact interactions, whereas resistance to etoposide and cytarabine requires contact interactions. 28 When primary AML samples (n 5 7) were treated with IL-6 and sIL-6Ra for 6 hours and then exposed to mitoxantrone for 18 hours, apoptosis was significantly reduced in cultures. A representative patient sample ( Figure 5C) and composite data from the seven tested samples are shown ( Figure 5D).…”
Section: Il-6 and Chemotherapy Resistancementioning
confidence: 98%